Philanthropic sales in live-streaming shopping: The impact of online interaction on consumer impulse buying - Ye, Yusen; Zhou, Zhili; Duan, Huawei (Frontiers in Psychology, 2022)
As philanthropic sales via live-streaming shopping have played an important role in alleviating the huge backlog of agricultural products during the outbreak of the COVID-19 pandemic, this paper aims to study how online interaction in philanthropic marketing exerts influence on consumer impulse buying behaviors. We empirically explore four major dimensions of online interactions in philanthropic live-streaming sales, i.e., the live streamers’ image, the herd effect of consumers, the responsiveness of sellers, and the mutual trust between consumers. The results reveal that the herd effect of consumers and the responsiveness of sellers could promote consumers’ empathy ability toward the growers of the products sold lively, whereas the live streamers’ image and the mutual trust between consumers have little effect on empathy promotions. Meanwhile, both the consumers’ empathy ability and the live streamers’ image positively affect consumers’ impulse buying behavior, which suggests a partial moderating role of consumers’ empathy ability. Lastly, by taking both social and business perspectives, we provide managerial implications for improving the effectiveness and efficiency of philanthropic live-streaming sales to alleviate social and economic pressure in emergencies.